Reconciling Growth and Sustainability through Circular Economy? - Wiesemann, Eva; Schmidt, Sabrina; Rubik, Frieder (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
With its promise of decoupling economic growth from resource use, the Circular Economy is gaining momentum in policy and businesses. But to live up to this promise, the gap between intention and implementation must be negotiated.